Asset Valuation in an Experimental Market - Forsythe, Robert; Palfrey, Thomas R.; Plott, Charles R. (Econometrica, 1982)
The time path of asset prices is studied within a stationary experimental environment. After several replications prices converge to a perfect foresight equilibrium. A sequential market having an "informational trap" and a futures market are also studied.